2021
DOI: 10.1002/adma.202104138
|View full text |Cite
|
Sign up to set email alerts
|

Defect‐Free Metal Deposition on 2D Materials via Inkjet Printing Technology

Abstract: 2D materials have many outstanding properties that make them attractive for the fabrication of electronic devices, such as high conductivity, flexibility, and transparency. However, integrating 2D materials in commercial devices and circuits is challenging because their structure and properties can be damaged during the fabrication process. Recent studies have demonstrated that standard metal deposition techniques (like electron beam evaporation and sputtering) significantly damage the atomic structure of 2D m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…1(h)], with HRS and LRS conductance of ∼0.01 μS and ∼0.05 S, respectively. The RS operation in these devices was shown [10] to be provoked by the creation and rupture of Ti-based CNFs across the h-BN stack, probably at the native defects embedded within the crystalline 2-D layered lattice, due to the lower energy for metal penetration at such sites [32].…”
Section: Resultsmentioning
confidence: 97%
“…1(h)], with HRS and LRS conductance of ∼0.01 μS and ∼0.05 S, respectively. The RS operation in these devices was shown [10] to be provoked by the creation and rupture of Ti-based CNFs across the h-BN stack, probably at the native defects embedded within the crystalline 2-D layered lattice, due to the lower energy for metal penetration at such sites [32].…”
Section: Resultsmentioning
confidence: 97%
“…106 However, inkjet printing deposition does not require a high-energy deposition process, resulting in defect-free metal deposition on 2D materials. 101 The authors reported that the metallic contacts deposited using inkjet printing could form a defect-less interface with the underlying h-BN layer. Additionally, as shown in Fig.…”
Section: D Vdw Ink Formulation Methodsmentioning
confidence: 99%
“…Recently, Zheng et al reported that inkjet printing can be a strategy for defect-free metal deposition on 2D vdW materials. 101 Contact engineering between the metal electrodes and underlying vdW materials has been intensively studied to improve charge injection at the contact to overcome the vdW gap. 52,53,[102][103][104][105] Additionally, Fermi level pinning effects originating from the interfacial states should be addressed in the field of 2D electronics.…”
Section: D Tmd-based Electronic Devices With Inkjet-printed Componentsmentioning
confidence: 99%
“…102 Mechanically flexible and optically transparent 2D materials have emerged as novel materials for fabricating flexible and printed electronics due to their excellent intrinsic mobility in atomically thin channel layers. [103][104][105][106] Inkjet-printed graphene electronics was first reported using exfoliated graphene ink dispersed in N-methyl-2-pyrrolidone (NMP). 103 Recently, transition metal dichalcogenide (TMDC) inks, including WSe 2 , WS 2 , MoS 2 , and MoS 2 , have also been reported for printed 2D transistors (Fig.…”
Section: Inks For Flexible Printed Electronic Devicesmentioning
confidence: 99%